Analysis Of The Health Level Of Cooperative Financial Statements With The Camels Method - Anantadjaya, Samuel PD; Hasibuan, Renika; Moridu, Irwan; Sumartono, Sumartono; HS, Sufyati (UNIVERSITAS PAKUAN, 2023)
The significance of health condition information regarding cooperatives for the management cooperative's continued existence or for third parties, including the general public and customers. By obtaining information regarding the cooperative's health condition, an assessment can be made of the cooperative's financial standing, whether it is deemed favorable or unfavorable, as well as its management and operational conditions. This data can then be utilized as a basis for future evaluations or decision-making by the cooperative. The present study employs the CAMELS method, which encompasses Capital, Asset Quality, Management, Earnings, Liquidity, and Sensitivity to Market Risk, to evaluate the soundness level of cooperatives. The objective of this study is to compare and contrast the cooperative health analysis method and the CAMELS method in terms of the health status of cooperatives. Descriptive comparative analysis was employed to examine a subset of cooperative financial reports spanning the years 2019 to 2022. This study employed descriptive statistics, a test for normality, and a paired sample t-test for analysis. Upon conducting an analysis utilizing descriptive statistics, normality tests, and paired sample t-tests, the distinction between the CAMELS method and the cooperative health analysis will become apparent. According to the results of the analysis test, the two approaches did not differ significantly. The fact that the acquisition of Sig. (2-tailed) is 0.881 indicates this. Where 0.881 is greater than 0.05. Consequently, no statistically significant distinction can be drawn between the two methods of cooperative health analysis.